Should Strategic Management Research Engage Public Policy Debates? - Barney, Jay B. (Academy of Management Journal, 2005)
The article discusses the multiple benefits of applying insights from strategic management theory to social policy analysis. For instance, strategic management theory can inform social policy responses to accounting scandals. Moreover, research in this area could also advance the development of strategic management studies. The general point is simple: By bringing strategic management theory to bear on critical social issues of the time, one will not only often elevate the level of debate, but also provide opportunities to test and extend the theory itself.